Investigation of Prospective Teachers' Ability to Determine Teaching Points in Bengkalis Folk Stories - Roziah, Roziah; Ariyanto, Joko; Puspita, Alvi; Nurhidayah, Nurhidayah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Bengkalis folklore is usually told or conveyed orally and has developed in writing. Bengkalis folk tales contain many teachings which will later be specialized to become part of the Malay Teachings (TAM). The purity of the teachings in this folklore should be enjoyed by all groups, including the younger generation. Prospective teachers play an active role in conveying all the Malay teachings contained in folklore to convey the wisdom contained therein. For this reason, the focus of this study is to answer two important questions, namely what the ability of prospective teachers is to find teaching guides and variants of teaching guides that have been successfully investigated by prospective Indonesian language teachers from the people of Bengkalis. This qualitative and quantitative research uses data from this study in the form of data excerpts taken from five Bengkalis folk tales, namely Disobedience; Awang Merah Merah Destroys Pirates; Commander of Bujang Kelana; Tragedy in the Land of Heirlooms; and a Brief History of Datuk Setia Indra Merbau. The findings of this study are that the five Bengkalis folk tales have Malay teachings as the basis or foundation of the Malay character who is obedient to parents and leaders, responsible, deliberative and brave